Fotodegradasi Diazinon Menggunakan Material Fotokatalis CaO Dari Cangkang Telur Dengan Bantuan Paparan Sinar Matahari - Auliya shofie; Hilman Imadul Umam; Teguh Pambudi; Andini Nur Aisyah; Keisha Ekya Larrisa (Fakultas Teknik Universitas Wahid Hasyim, 2026)
The increasing use of pesticides in agriculture contributes to water pollution, particularly from diazinon, a toxic and persistent compound. Photodegradation using waste-based catalysts offers a promising remediation approach. This study aims to synthesize calcium oxide (CaO) from eggshell waste and evaluate its photocatalytic performance for diazinon degradation under sunlight. An experimental method was employed, varying catalyst dosage, pH, initial diazinon concentration, and irradiation time, with degradation efficiency as the response variable. CaO was synthesized via calcination at 800°C, followed by KOH activation. Characterization revealed a porous surface structure with irregular particle distribution and the presence of Ca–O and O–H functional groups. UV–Vis analysis indicated a band gap of 2.75 eV, suggesting activity under solar irradiation. Optimal conditions were achieved at 16 mg catalyst dosage, pH 7, 50 ppm diazinon, and 90 minutes irradiation, yielding 26.41% degradation efficiency. Kinetic analysis followed a pseudo-second-order model (k = 0.0181; R² = 0.9977). These results demonstrate that eggshell-derived CaO is a low-cost, eco-friendly photocatalyst for pesticide wastewater treatment.